Analysis of the efficiency of higher education systems - Tóth, Réka (Acta Agraria Debreceniensis, 2009)
The aim of the higher education reform process both in Hungary and in the European countries is establishing a competitive, qualitative higher education. The Education Minister of our country regularly emphasizes in his statements that the quantitative changes of he past 15 years are completed, from now the emphasis must be on quality :„a degree in itself is not sufficient, the actual knowledge behind is necessary”. To achievethis aim, the government carried out several changes in the field of higher education in the past years, one of them was implementing a budget support system in accordance with the performance of the institutions. The objective of the three year long support agreement between the state and the higher education institutions is considering quality parameters and outputs beside and instead of normative (input-based) support. The other occurent and debated issue is the introduction of tuition fees. Although this plan was rejected by the national referendum on 9th March, 2008, some weeks ago an amendment bill was passed, which would mean bringing tuition fees back in the system.In my paper I am examining whether the efficiency of higher education systems are influenced by the extent of the contribution of the state and the private sector to their expenses. Furthermore I’d like to find the answer to the following question: Does it matter what principles and mechanisms play role by the distribution of the state support between the institutions of higher education.